A Pragmatic Analysis of Love Expression in Mixed Blessing Translated Into Berkah Penuh Cobaab by Danielle Steel - ARYANIK., PIPIT (2011)
This study deals with: (1) the variation of the language form of love expressions in Mixed Blessing translated into Berkah Penuh Cobaan by Danielle Steel, and (2) the equivalence of the intention of love expressions Mixed Blessing translated into Berkah Penuh Cobaan by Danielle Steel. The type of this research is descriptive qualitative research, by which the object is love expressions in Mixed Blessing translated into Berkah Penuh Cobaan by Danielle Steel. In order to collect the data, the writer must, first read the novel, second classify the words or sentences of Love Expressions, and then the last give codes the data. The results of the study shows that, (1) there are three types of sentence for love expressions, they are declarative sentence (I love you, dad, she whispered nervously), imperative sentence (Don't be sensitive, Di. We just want to know what's happening with you, that's all. We love you), and interrogative sentence (What's bothering you, sweetheart? I wish you would tell me He knew it had to be important, if she'd called Marina). (2) there are six intentions of love expressions, namely showing affection (I'm glad you're happy, sweetheart, Andy whispered to her that night), showing care (Take care, he said quietly, and then they left), showing eagerness (I wish today is never end, she said, closing her eyes, and thinking of how wonderful it had been), showing engagement (I promise I'll make it as easy as I can), showing persuasion (You look absolutely gorgeous!, he raved appreciatively and she grinned), and showing praise (You're a beautiful bride, barb, Mark told her as they dance slowly around the floor).